Engineering speaking by design delivering technical presentations with real impact /cEdward J. Rothwell, Michael J. Cloud - Rothwell, Edward J. (CRC Press, 2015)
From the Authors of Engineering Writing by Design: Creating Formal Documents of Lasting ValueEngineering presentations are often a topic of frustration. Engineers complain that they don't enjoy public speaking, and that they don't know how to address audiences with varying levels of technical knowledge. Their colleagues complain about the state of information transfer in the profession. Non-engineers complain that engineers are boring and talk over everybody's heads.Although many public speaking books exist, most concentrate on surface issues, failing to distinguish the formal oral technical